Disiplin Membaca Alkitab dan Berdoa bagi Pertumbuhan Rohani Remaja: Studi pada Remaja di gereja Kristen Sulawesi Barat Bukit Zion, Mamuju - Maya YM (Sekolah Tinggi Teologia Kerusso Indonesia, 2023)
The church has a vital role in building the spiritual life of every congregation member. This includes teenagers, for whom it is essential to receive attention and be educated in their faith to grow in the true knowledge of Jesus Christ and live in harmony with God's Word. Adolescence is a crucial period of growth in finding self-identity, so spiritual life must be a concern. They must be educated through the habit of reading the Bible and in an atmosphere of prayer so that they live in the corridors that the Bible teaches and are not easily swayed by the currents of the world, which can drag them away from God. So, this research aims to determine the extent of the influence of discipline in reading the Bible and praying on the spiritual growth of teenagers. The method used in this research is quantitative. After conducting research at GKSB Bukit Sion Mamuju involving 36 teenagers from GKSB Bukit Sion Mamuju to find out the influence of the discipline of reading the Bible and praying on the spiritual growth of GKSB Bukit Sion Mamuju teenagers, it was concluded that reading God's Word and praying had a significant influence on the spiritual development of GKSB Bukit Sion Mamuju.